Relationships between urban tree communities and the biomes in which they reside. Issue 1 (24th May 2012) - Ramage, Benjamin S.; Roman, Lara A.; Dukes, Jeffrey S.
Abstract: Questions: Climate strongly influences the composition of natural plant communities, but a variety of human activities might release plants in urban areas from some of these climatic constraints. (1) After controlling for minimum temperature, is urban tree species composition related to biome? (2) Do any such patterns result solely from the presence of native species in urban floras? (3) Which climatic, demographic and economic variables are predictive of urban tree species composition? Location: Continental USA. Methods: We investigated patterns of tree species composition in small cities across the continental USA, specifically exploring relationships to surrounding biomes and their accompanying temperature and precipitation regimes, as well as to key demographic and economic variables. We estimated urban tree species composition by surveying tree experts in randomly selected cities that were stratified by minimum temperature (i.e. 'hardiness zone') and biome, and constrained to similar population sizes. We then used non‐metric multidimensional scaling to investigate relationships between urban tree species composition, biome classification, native status, individual climate variables and several anthropogenic factors. Results: We found that urban tree communities were consistently related to the surrounding biome, even after controlling for minimum temperatures. These communities could also be predicted by several individual climatic variables (in models that focused solely on the role of climate as well as models that simultaneously considered key anthropogenic factors). In addition, most of these general patterns were still present when we exclusively examined non‐native species. We were unable to identify specific climatic and anthropogenic variables of broad importance because the most predictive variables were highly dependent upon the specific analysis. Conclusions: Our results demonstrate that, despite substantial human influence, urban tree communities (including their non‐native components) are related to the same climate factors that shape wildland plant communities. Abstract : We investigated patterns of tree species composition in small cities across the continental United States. We found that urban tree communities (including their non‐native components) were related to the surrounding biome even after controlling for minimum temperatures and anthropogenic factors. Despite substantial human influence, urban tree communities are connected to the same climatic factors that shape wildland plant communities.